Influence of 3-(3-fluorophenyl)-6-(4-methoxyphenyl)-7h-[1,2,4]-triazolo-[3,4-b] [1,3,4] thiadiazine on the cultural properties of pathogenic М. bovis - Bihdan, Oleksii; Бігдан, Олексій Антонович; Parchenko, Volodymyr; Парченко, Володимир Володимирович; Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Зажарський, Володимир Володимирович; et al. (My University, 2018)
Derivatives of 1,2,4-triasole are widely used in many fields of human activity. Regular creation of new and modern drugs. The outstanding scientists are actively working in this direction and this gives its results. Today, the treatment and prevention of many types of tuberculosisis a priority task in many countries around the world. The purpose of our work is to investigate the effect of 3- (3-fluorophenyl) -6- (4-methoxyphenyl) -7H- [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazine on the cultural properties of pathogenic Mycobacteriumbovis. Having analyzed the results of the conducted studies, the effect of 3- (3-fluorophenyl) -6- (4-methoxyphenyl) -7H- [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazine on the cultural properties of pathogenic Mycobacteriumbovis. According to the results of an experimental study, the effect of 3-(3-fluorophenyl)-6-(4-methoxyphenyl)-7H-[1,2,4]-triazolo-[3,4-b][1,3,4]thiadiazine on the cultural properties of pathogenic Mycobacterium bovis. It has been found that the compound in various effective concentrations has a tuberculostatic effect. Positive influence on this type of biological activity different pH valuesof the medium and temperature regimes. Thus, it should be noted the need for further in-depth studies of this compound that can be used in the future to create new original drugs. Синтез та дослідження впливу нових по-хідних 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину на культурні ознаки пато-генного M. bovis. Проблематика побічного впливу ксенобіотиків та протидія їх токсичному впливу залишаються надзви-чайно значними. Стійкий туберкульоз є серйозною проблемою охорони здоров'я населення у багатьох країнах, що розви-ваються. Лікування такої форми туберкульозу зай-має більше часу і вимагає все більш дорожчi ліки. Метою даної роботи є синтез та дослідження нових похідних 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину та їх здатність впливати на культурні ознаки патогенний M. bovis. Об'єктом дослідження є нові похідні 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину. Вирощування патогенних штамів M. bovis проводили при температурі 37 градусів С в середовищі рН 6,5 і 7,1, де додатково синтезовані сполуки в масових концентраціях 0,1; 0,5; 1%. Як порівняльна субстанція - класична субкультура. В результаті проведених досліджень було зроблено висновок, що найбільше виражений туберкулоцидний вплив серед аналізованих сполук мав 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину.
Вплив 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину на культуральні властивості патогенного М. bovis
Keywords: M. bovis; М. bovis; synthesis; синтез; antituberculosis action; боротьба з туберкульозом; 3-(3-fluorophenyl)-6-(4-methoxyphenyl)-7h-[1,2,4]-triazolo-[3,4-b][1,3,4]thiadiazine; 3-(3-фторфеніл)-6-(4-метоксифеніл)-7Н-[1,2,4] триазоло [3,4-в] [1,3,4] тіадіазину